Remote temperature monitoring system for strengthening cold chain management: Belize experience - Oladeji, Olusola; Beer, Natalia Largaespada; Baitwabusa, Angella Edith; Can, Edgar; Middleton, Lilian; Cabral, Greg Mitchell (International Journal Of Community Medicine And Public Health, 2025)
The ability to monitor vaccines for optimal temperatures throughout the supply chain is a cornerstone of successful immunization programmes. This study aimed to describe the process of deployment of remote temperature monitoring devices to strengthen cold chain system in Belize and assess the effectiveness of the use of the technology. An exploratory study and used mix of qualitative and quantitative methods. The qualitative data was extracted from the project reports and Key Informant interviews (KII). The quantitative method used retrospective review of records of temperature alarms between November 2023 and October 2024. The result is organized into two parts (A) The description of the process for the deployment of the RTM system (B) Program results. Eighteen alarms were reported in 8 months from four of the eight devices (installed at the national and subnational level) which ranged from one alarm per month to 6 alarms per month with average of 2.6 alarms per month. The duration of each alarm was from 0.6 hour to 31.3 hours with average of 9.6 hours and 75% of the alerts resolved within 24 hours. The result of the KII is organized into two themes. The first theme was related to the perception and experience of health workers on the use of the devices in improving temperature monitoring and the second theme was related to the health system support in ensuring timely response to temperature excursions. The study contributes to existing knowledge on the use of remote temperature monitoring system to improve cold chain management.